2018
DOI: 10.1016/j.psep.2017.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Comparing two enhancing methods for improving kitchen waste anaerobic digestion: Bentonite addition and autoclaved de-oiling pretreatment

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…The methane content in biogas decreased with increasing OLR in both reactors ( Table 1), meaning that methanogenesis was diminished by increased organic load. Similar observations of methane content reduction with increasing OLR, particularly under overloading conditions, have been reported in previous studies [35,36]. It is notable that the decrease in methane content was far more significant in RT than in RM, particularly at an OLR of 1.0 g COD/L·d.…”
Section: Temperature Effects On Methanogenesis and Sulfidogenesissupporting
confidence: 89%
“…The methane content in biogas decreased with increasing OLR in both reactors ( Table 1), meaning that methanogenesis was diminished by increased organic load. Similar observations of methane content reduction with increasing OLR, particularly under overloading conditions, have been reported in previous studies [35,36]. It is notable that the decrease in methane content was far more significant in RT than in RM, particularly at an OLR of 1.0 g COD/L·d.…”
Section: Temperature Effects On Methanogenesis and Sulfidogenesissupporting
confidence: 89%
“…These results show that the application of bentonite in WAS/KW co-digestion could neutralize excessive VFAs in digester, and thus stabilize anaerobic system. Zhang [34] also found that adding bentonite to the anaerobic digestion of kitchen waste can prevent volatile fatty acids (VFA) accumulation and obtain a high methane production at low OLR (1.39 gVSL -1 d -1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A low pH or high concentration of VFAs indicates that the system may be acid inhibited. The optimal pH range for methanogenic microorganisms is about 6.50-8.20, beyond which they are inhibited, and their metabolic activity slows down (Zhang et al 2018). The initial pH of every digester was adjusted to 7.00 + 0.10 (Figure 2(a)), which falls within the growth range suitable for anaerobic microorganisms.…”
Section: Changes In Ph and Vfas In The Reaction Systemmentioning
confidence: 99%